The madhatter project. - Hultkrans, Andrew (Artforum International)
Reports on the federal government's crackdown on hackers in the United States. Threat of computer hacking faced by the government and the private sector; Insight on the culture of hackers and their popularity in media; Background on the first wave of hacker crackdowns started in 1990; Investigations conducted by law enforcement agencies.